Scaling of spectral displacement ordinates with damping ratios. - Bommer, Julian J. (Earthquake engineering & structural dynamics.)
The next generation of seismic design codes, especially those adopting the framework of performance-based design, will include the option of design based on displacements rather than forces. For direct displacement-based design using the substitute structure approach, the spectral ordinates of displacement need to be specified for a wide range of response periods and for several levels of damping. The code displacement spectra for damping values higher than the normal value of 5 percent of critical will generally be obtained, as is the case in Eurocode 8 and other design codes, by applying scaling factors to the 5 percent damped ordinates. These scaling factors are defined as functions of the damping ratio and, in some cases, the response period, but are independent of the nature of the expected ground shaking. Using both predictive equations for spectral ordinates at several damping levels vary with stochastic simulations, it is shown that the scaling factors for different damping levels vary with magnitude and distance, reflecting a dependence of the scaling on the duration of shaking that increases with the damping ratio. The options for incorporating the influence of the factor into design code specifications of displacement response spectra are discussed.